Determinants of mobile banking adoption:A comparative study between U.S. and Thailand - Chuleeporn Changchit (2018)
Copyright © 2018, IGI Global. With a rapid increase in smart phone users, mobile banking is becoming an available banking channel that allows consumers to perform banking transactions at their own convenience. However, not all customers are ready to embrace this new channel of services. It is crucial for banks to fully understand the preferences of their customers, especially which factors play an important role in encouraging or discouraging customers from using this banking channel. It is also important to further investigate whether their customers' perceptions on mobile banking is influenced by culture. This article aims at comparing the mobile banking perceptions between the consumers in the U.S. and in Thailand. The research findings reveal the various factors that influence mobile banking adoption for these two nationalities. The results should help banks gain an understanding of these factors, and thus direct their efforts to develop features that satisfy the needs of their target customers and alter their business model to promote factors that have a positive influence on mobile banking adoption.